2020
DOI: 10.1044/2019_persp-19-00072
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Benefits of Engaging Undergraduate Researchers in Conducting a Systematic Literature Review

Abstract: Purpose This project used a reflective practice framework to examine outcomes of an undergraduate student–faculty collaborative research project. The project examined benefits of undergraduate contributions to a large-scale systematic review and explore benefits to the students. Conclusions Throughout a large literature search process, two student researchers documented their reflections, including field notes and written reflections about their persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The Land and Booth (2020) course was scheduled in the penultimate year of the program in order to provide students with the skills needed to conduct a systematic review/meta-analysis capstone project in the final year. Case studies and student reflections have shown that students perceive their participation in systematic reviews as leading to their growth as student learners and researchers, and helps form their identities as academics (Look et al, 2020;Pickering et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The Land and Booth (2020) course was scheduled in the penultimate year of the program in order to provide students with the skills needed to conduct a systematic review/meta-analysis capstone project in the final year. Case studies and student reflections have shown that students perceive their participation in systematic reviews as leading to their growth as student learners and researchers, and helps form their identities as academics (Look et al, 2020;Pickering et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There was no uniformity in the number of peerresearchers involved in the consulted systematic reviews: it varied from one [21] to three [19] Two articles included two peer-researchers (18,20). None of the seven articles described a rationale as to why they chose a certain number of peer researchers.…”
Section: Fig 2 Literature Searching and Sorting For Selecting Scholar...mentioning
confidence: 99%
“…There is a diversity in characteristics of peerresearchers involved in the different articles. Four articles reported the involvement of patients as peer researchers [18,19,20,21], one study mentions salaried workers, health trainers, volunteer health champions, and program coordinators as peer researchers [22], while in one other study undergraduate students were mentioned as peer researchers, and in another study members of Canada's indigenous community (from Nunatsiavut) were included as peer researcher [22].…”
Section: Fig 2 Literature Searching and Sorting For Selecting Scholar...mentioning
confidence: 99%
See 2 more Smart Citations